Protoide. šaknis *leh3u- „lietis, tekėti…“ baltų kalbose (liet. liūtìs ir lietùs) - Karaliūnas, Simas (Baltistica, 1992)
THE PROTOIDE. ROOT *leh3u- “flow, stream, pour…” IN BALTIC (LITH. liūtìs “heavy shower, downpour” AND lietùs “rain”)The relationship of Lith. liū́tis/liūtìs “heavy shower, downpour” and lietùs “rain”, as has been suggested by P. Skardžius, may be understood only in the Protoindoeuropean prospect. Hit. lahui “it flows, streams, pours…”, Gr. λoύει “he bathes, washes” and Lat. lavit “id.” seem to have the apophonic o and their protoform should be reconstructed as *leh3-e/o, as proposed by F. Bader. Its root vocalism e is attested in Mycenaean Gr. re-wo-te-re-jo and Lith. liaũkti (-ia) “flow, stream”
Keywords: liūtis; lietus; baltų kalbos; etimologija